Application of NiCu (at) rGO / Mg (OH) 2 composite catalytic material in catalytic hydrogenation and dehydrogenation of liquid organic hydrogen carrier

By using NiCu@rGO/Mg(OH)2 composite catalytic material in liquid organic hydrogen support for hydrogenation and dehydrogenation reaction, the problems of high cost and complexity of precious metal catalysts in the prior art are solved, and low cost is achieved. The efficient hydrogen storage effect of hydrogen gas has promoted the development of liquid organic hydrogen storage technology.

CN119236945APending Publication Date: 2025-01-03NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411255435.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing liquid organic hydrogen support catalysts have problems such as high amount of precious metals, high cost, and difficult to control reaction complexity and selectivity, which leads to high hydrogen storage costs and low efficiency, limiting the widespread application of hydrogen energy.

Method used

The NiCu@rGO/Mg(OH)2 composite catalytic material is used to carry out hydrogenation and dehydrogenation reaction in a liquid organic hydrogen support, and catalyzed through specific preparation processes and conditions (such as catalyzing under a hydrogen atmosphere or vacuum environment, with a temperature of 150℃- 200℃, pressure 5MPa-7MPa, time 5-7 hours, mass ratio is 1:8-12) to improve catalytic performance.

Benefits of technology

It achieves low-cost and efficient catalytic performance, reduces the complexity of hydrogenation and dehydrogenation devices, improves the hydrogen storage efficiency and safety of hydrogen, and reduces the cost of hydrogen storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236945A_ABST
    Figure CN119236945A_ABST
Patent Text Reader

Abstract

The invention relates to an application of a NiCu (at) rGO / Mg (OH) 2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier, a hydrolysis product of a magnesium hydride-based hydrolysis hydrogen production material is filtered and dried and is used as a liquid organic hydrogen storage catalyst in the catalytic hydrogenation and dehydrogenation of the liquid organic hydrogen carrier, and the advantages of resource recycling and the like are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid organic hydrogen storage catalyst, and in particular to an application of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier. Background Art

[0002] At present, renewable energy has become a key technical means to solve the energy crisis and environmental pollution problems. Hydrogen energy has the advantages of high combustion calorific value, no pollution, wide sources, and renewable, making it an ideal green energy medium, a potential environmentally clean fuel and energy, and an important part of renewable energy. However, at present, the extremely low volume density of hydrogen (0.08988g / L at 1atm) seriously hinders the storage and utilization of hydrogen, making its storage and transportation efficiency low. The inability to achieve large-scale, low-cost storage and transportation is one of the technical bottlenecks limiting the widespread application of hydrogen energy.

[0003] For traditional compressed hydrogen and cryogenic liquid hydrogen storage methods, there are problems such as low safety, high energy consumption, and high cost of establishing new hydrogenation systems, which greatly hinder the development of large-scale application of hydrogen. In recent years, among chemical hydrogen storage materials, liquid organic hydrogen carrier (LOHC) has attracted widespread attention as a promising hydrogen storage medium. In this concept, H2 is chemically stored in organic compounds through an exothermic hydrogenation reaction, and the hydrogen-rich compound (i.e., LOHC) exists in liquid form under ambient conditions (such as conventional fuels such as gasoline and diesel). When stored in LOHC, hydrogen can be transported using the already built conventional fuel infrastructure; in addition, the reaction heat required for the endothermic dehydrogenation reaction is much lower than other hydrogen production processes, allowing the hydrogen to be released again at a specific location.

[0004] At present, although LOHC compounds have very useful hydrogen storage properties, as well as economical, safe, and easy-to-manage operations; LOHC hydrogen storage media still have problems such as complexity and diversity of reactions, high activation energy, difficult to control reaction selectivity, and incomplete dehydrogenation. In addition, due to the large amount of precious metal catalysts used in LOHC, the cost is relatively high; in addition, the problem of corresponding catalysts that can be highly selective in hydrogenation and dehydrogenation reactions has not been solved. Therefore, the catalyst is a key component of the entire LOHC hydrogen storage process. High-efficiency and long-life catalysts can not only reduce costs, but also reduce reaction temperatures, increase reaction rates and conversion rates.

[0005] Conventional liquid organic hydrogen storage catalysts have the disadvantages of high precious metal usage and high cost, which are not conducive to the practical application of organic liquid hydrogen storage. Compared with precious metal catalysts, cheap transition metal (Ni, Co, Fe) catalysts have become effective alternatives to catalysts in the development of new catalytic systems due to their low cost, unique electronic structure, and good activity and selectivity in catalytic hydrogenation reactions. Therefore, exploring low-cost and efficient catalysts is an urgent problem to be solved. The development of efficient and low-cost hydrogenation and dehydrogenation catalysts can effectively reduce the complexity of hydrogenation and dehydrogenation equipment, while greatly reducing the cost of hydrogen storage; realizing the advantages of high density, high hydrogen storage efficiency, and high safety of organic liquid hydrogen storage, thereby promoting the large-scale application and development of liquid organic hydrogen storage technology, making it one of the most promising hydrogen storage methods in the future. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a NiCu@rGO / Mg(OH)2 composite catalytic material for the application of liquid organic hydrogen carrier catalytic hydrogenation and dehydrogenation

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The present invention provides an application of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier.

[0009] Furthermore, when used for catalytic hydrogenation and dehydrogenation, the NiCu@rGO / Mg(OH)2 composite catalytic material is mixed with a liquid organic hydrogen carrier to be hydrogenated or dehydrogenated to carry out catalytic hydrogenation or dehydrogenation.

[0010] Furthermore, when catalytic hydrogenation is performed, the reaction system consisting of the NiCu@rGO / Mg(OH)2 composite catalytic material and the liquid organic hydrogen carrier is under a hydrogen atmosphere;

[0011] Furthermore, when catalytic dehydrogenation is performed, the reaction system consisting of the NiCu@rGO / Mg(OH)2 composite catalytic material and the liquid organic hydrogen carrier is in a vacuum environment.

[0012] Furthermore, when catalytic hydrogenation and dehydrogenation are carried out, the reaction system is at a temperature of 150° C.-200° C., a pressure of 5 MPa-7 MPa, and a time of 5-7 h.

[0013] Furthermore, the mass ratio of the NiCu@rGO / Mg(OH)2 composite catalytic material to the liquid organic hydrogen carrier is 1:8-12.

[0014] Furthermore, the liquid organic hydrogen carrier is ethylcarbazole.

[0015] Furthermore, the NiCu@rGO / Mg(OH)2 composite catalytic material is prepared by the following steps:

[0016] (1) Methanol was added to Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, GO and PVP, fully dissolved, stirred and dried to obtain NiCu@GO powder.

[0017] (2) placing the NiCu@GO powder obtained in step (1) into a tubular furnace and calcining it twice to obtain a bimetallic NiCu@rGO catalyst,

[0018] (3) mixing the bimetallic NiCu@rGO catalyst obtained in step (2) with a Mg source, and ball milling the mixture to obtain an additive composite material of a Mg source-NiCu@rGO.

[0019] (4) The Mg source-NiCu@rGO additive composite material obtained in step (3) is hydrolyzed, filtered, and dried to obtain a NiCu@rGO / Mg(OH)2 composite catalyst.

[0020] Furthermore, in step (1), the mass ratio of methanol, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, GO and PVP is 4-10:100-200:100-200:4-10:1, the stirring time is 4-10h, the rotation speed is 50-200rpm, the drying time is 10-24h, and the temperature is 50-100℃.

[0021] Furthermore, during the two calcinations in step (2), the first calcination is carried out in an Ar atmosphere at 4-10°C min -1 Heat to 400-600℃ at a heating rate of 1000℃, keep warm for 4-10h and then cool down naturally;

[0022] The second calcination was carried out in a H2 / Ar atmosphere with a H2 ratio of 5% at 4-10°C min -1 Heat to 400-600℃ at a heating rate of 1000℃, keep warm for 4-10h and then cool down naturally.

[0023] Furthermore, in step (3), the Mg source is MgH2 or Mg, and the mass ratio of the bimetallic NiCu@rGO catalyst to the Mg source is 1:1-20;

[0024] The ball milling is carried out under an argon atmosphere, with a ball-to-material ratio of 5-50:1, a ball milling speed of 300-500 rpm, and a ball milling time of 5-50 h;

[0025] The drying temperature in step (4) is 40-100° C. and the drying time is 10-24 hours.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] Compared with traditional liquid organic hydrogen storage catalysts, the NiCu@rGO / Mg(OH)2 composite catalytic material has lower cost, good catalytic performance, high liquid organic hydrogen carrier capacity retention rate, and the preparation process provided by the present invention is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of a hydrolysis device used in the present invention;

[0029] Figure 2 TEM electron microscope image of NiCu@rGO / Mg(OH)2 composite catalyst sample;

[0030] Figure 3 Field emission scanning electron microscopy images and element distribution maps of NiCu@rGO-based composites;

[0031] Figure 4 Field emission scanning electron microscopy image and element distribution map of NiCu@rGO / Mg(OH)2 hydrolysis product;

[0032] Figure 5 This is the XRD pattern of the NiCu@rGO / Mg(OH)2 composite catalyst sample;

[0033] Figure 6 XPS spectra of the hydrolysis products of MgH2-NiCu@rGO composite materials, a is the XPS spectrum of Cu 2p, b is the XPS spectrum of Ni 2p;

[0034] Figure 7 The product of the NiCu@rGO / Mg(OH)2 composite catalyst after hydrogen absorption catalysis of ethylcarbazole 1 H-NMR performance test diagram;

[0035] Figure 8 The product of the NiCu@rGO / Al2O3 composite catalyst after hydrogen absorption catalysis of ethylcarbazole 1 H-NMR performance test diagram;

[0036] Fig. 9 This is a test chart of the hydrogen absorption catalytic performance of Pd / Mg(OH)2 composite catalyst on ethylcarbazole. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0038] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.

[0039] The hydrolysis reaction of the experimental materials to produce hydrogen was tested using a homemade device, such as Figure 1 As shown in the figure, the device is mainly composed of a reaction part and a collection and recording part. The reaction part consists of a 50mL flask reactor, a constant temperature stirring reaction bath and a syringe, and the collection and recording part consists of a gas washing bottle, a beaker, an electronic balance and a computer connected to the balance. At the beginning of the hydrolysis experiment, the hydrolysis experimental device should be tested for air tightness to prevent leakage during hydrolysis. To ensure the accuracy of the test, the gas washing bottle should be filled with deionized water and no large amount of gas should be left. When doing hydrolysis experiments at different temperatures, preheat the reaction solution with a constant temperature stirring reaction bath in advance to ensure that the temperature of the hydrolysis reaction solution is consistent with the temperature required for the experiment. During hydrolysis, 50mg MgH2-NiCu@rGO was loaded into a 50mL flask reaction container in the glove box, taken out of the glove box and quickly connected to the hydrolysis reaction device, and then 10mL of aqueous solution was quickly injected into the flask reaction container through a syringe. The generated hydrogen discharged the water in the gas washing bottle into the beaker, and the mass of the water in the beaker was recorded in real time by an electronic balance connected to a computer. A constant temperature stirring reaction bath is used to control the flask. An electronic balance is used to measure the mass of water replaced by the escaped hydrogen. The reading on the balance is the volume of hydrogen produced by hydrolysis. The volume of H2 produced by hydrolysis is equal to the reading on the balance. The electronic balance is connected to a computer, which can automatically record the data and reaction time.

[0040] Example 1

[0041] 100 mL of methanol was added to Ni(NO3)2·6H2O (2855 mg), Cu(NO3)2·3H2O (2372 mg), GO (800 mg) and PVP (16 mg), and ultrasonic oscillation was performed until all of them were dissolved to form a transparent solution, and then stirred for 8 h. The solution was then placed in a blast oven and dried for 24 h at a drying temperature of 50 °C to obtain NiCu@GO. The NiCu@GO powder prepared above was spread in a crucible and placed in a tube furnace cavity. It was first heated at 5 °C min under an Ar atmosphere. -1 The temperature was then raised to 500 °C at a rate of 5 °C min-1 and then cooled naturally in a H2 / Ar atmosphere with a H2 ratio of 5%. -1The reaction mixture was heated to 500 °C at a heating rate of 1.5 ℃, and then cooled naturally after being kept at this temperature for 6 h to obtain a highly dispersed bimetallic NiCu@rGO catalyst. Figure 3 The field emission scanning electron microscope image and element distribution map of NiCu@rGO-based composite materials. The additive composite material of MgH2-NiCu@rGO was prepared by ball milling. The mechanical grinding was carried out for 10 hours. The ball milling process was carried out on a ball mill (FRITSCH 06.2000 / 04350). The ball-to-material ratio during ball milling was 30:1. The rotation speed was 400rpm under argon atmosphere. The amount of MgH2 was 0.9g and the amount of NiCu@rGO was 0.1g. Figure 1 As shown, the ground MgH2-NiCu@rGO-based composite material was hydrolyzed and the hydrolyzate was filtered to obtain the hydrolyzate. Figure 6 The XPS spectrum of the hydrolysis product of the MgH2-NiCu@rGO composite material was obtained by drying it in a forced air oven at 80°C for 20 hours to obtain a NiCu@rGO / Mg(OH)2 composite catalyst. Figure 2 TEM electron microscope photo of NiCu@rGO / Mg(OH)2 composite catalyst sample. Figure 5 This is the XRD spectrum of the NiCu@rGO / Mg(OH)2 composite catalyst sample.

[0042] Ethyl carbazole and NiCu@rGO / Mg(OH)2 composite catalyst were added into a high-temperature and high-pressure reactor in a mass ratio of 10:1. The high-temperature and high-pressure reactor was connected to a hydrogen reservoir. The catalytic hydrogenation and dehydrogenation chemical performance tests of ethyl carbazole were carried out in the high-temperature and high-pressure reactor at a temperature of 170°C and a pressure of 6MPa for a reaction time of 6 hours.

[0043] Figure 7 The product of the NiCu@rGO / Mg(OH)2 composite catalyst after hydrogen absorption catalysis of ethylcarbazole 1 H-NMR performance test chart, under the reaction conditions of 170 ℃, 6MPa and 6h reaction time, reaction pressure conditions and catalysis, the conversion rate of ethylcarbazole is 98.9% and 5.68wt.% of hydrogen is released.

[0044] Comparative Example 1

[0045] 100 mL of methanol was added to Ni(NO3)2·6H2O (2855 mg), Cu(NO3)2·3H2O (2372 mg), GO (800 mg) and PVP (16 mg), and ultrasonic oscillation was performed until all of them were dissolved to form a transparent solution, and then stirred for 8 h. The solution was then placed in a blast oven and dried for 24 h at a drying temperature of 50 °C to obtain NiCu@GO. The NiCu@GO powder prepared above was spread in a crucible and placed in a tube furnace cavity. It was first heated at 5 °C min under an Ar atmosphere.-1 The temperature was then raised to 500 °C at a rate of 5 °C min-1 and then cooled naturally in a H2 / Ar atmosphere with a H2 ratio of 5%. -1 The reaction mixture was heated to 500°C at a heating rate of 100°C, kept warm for 6 hours, and then cooled naturally to obtain a highly dispersed bimetallic NiCu@rGO catalyst. Weigh 4.5g Pl23, add 100ml anhydrous ethanol and stir to dissolve. Take 7.5ml of concentrated nitric acid and add it to the above solution, add 10.2g of aluminum isopropoxide, and continue stirring for 5 hours to completely dissolve the aluminum isopropoxide. The NiCu@rGO catalyst was placed in the solution and stirred evenly for 10 hours. The above sol was placed in a 60°C oven and aged for 48 hours. A light yellow dry gel was obtained. The gel was placed in a muffle furnace and programmed to heat up (2°C / rain) to 400°C, calcined for 4 hours, and then heated (5°C / min) to 600°C and calcined for 1 hour. The NiCu@rGO-Al2O3 catalyst was obtained.

[0046] Ethyl carbazole and NiCu@rGO-Al2O3 catalyst were added into a high-temperature and high-pressure reactor in a mass ratio of 10:1. The high-temperature and high-pressure reactor was connected to a hydrogen reservoir. The catalytic hydrogenation and dehydrogenation chemical performance tests of ethyl carbazole were carried out at a temperature of 170°C and a pressure of 6MPa for a reaction time of 6 hours in the high-temperature and high-pressure reactor.

[0047] Figure 8 The product of the NiCu@rGO / Al2O3 composite catalyst after hydrogen absorption catalysis of ethylcarbazole 1 H-NMR performance test chart, under the reaction conditions of 170 ℃, 6MPa and 6h reaction time, reaction pressure conditions and catalysis, the conversion rate of ethylcarbazole is 97.3% and 5.63wt.% of hydrogen is released.

[0048] Comparative Example 2

[0049] 100 mL of Na2CO3 aqueous solution (0.5 M) was quickly added to 400 mL of Mg(NO3)2 aqueous solution (0.125 M) and stirred vigorously at room temperature. After 10 minutes, it was filtered and washed with deionized water, and then dried under reduced pressure to obtain MgCO3 powder. The obtained MgCO3 powder was transferred to a crucible and calcined at 500°C for 2 hours in an air atmosphere. The heating rate should be controlled at 2°C min-1. After cooling to room temperature, MgO was collected for the next step. The hydrolysis of MgO was carried out at room temperature, and MgO was added to deionized water (1 mg / mL) under stirring. The dispersion gradually became a colloidal suspension, showing an obvious pearlescent effect, indicating that a lamellar structure was formed. After 1 hour, the product was collected by filtration and dried under reduced pressure, and the obtained sample was named Mg(OH)2-NS. The preparation of Pd / Mg(OH)2 catalyst is as follows: 0.5 wt% of Pd was loaded on Mg(OH)2-NS, and the dehydrogenation catalyst was prepared by incipient wetness impregnation (IWI). First, 0.84 g of PdCl2 solution (1 wt%) was added dropwise to 1 g of Mg(OH)2-NS, stirred at room temperature for 3 h, and then evaporated in a water bath at 80°C. Finally, the sample was dried in a vacuum drying oven at 80°C and named Pd / Mg(OH)2.

[0050] Ethyl carbazole and Pd / Mg(OH)2 were added into a high-temperature and high-pressure reactor in a mass ratio of 10:1. The high-temperature and high-pressure reactor was connected to a hydrogen reservoir. The catalytic hydrogenation and dehydrogenation chemical performance tests of ethyl carbazole were carried out in the high-temperature and high-pressure reactor at a temperature of 170°C and a pressure of 6 MPa for a reaction time of 6 hours.

[0051] Fig. 9 This is a test chart of the hydrogen absorption catalytic performance of ethyl carbazole by Pd / Mg(OH)2 composite catalyst. Under the reaction conditions of 170℃, 6MPa and 6h, reaction pressure conditions and catalytic action, the conversion rate of ethyl carbazole is 100% and 5.72wt.% of hydrogen is released.

[0052] The catalytic materials and reaction results of Example 1 and Comparative Examples 1-2 are as follows

[0053]

[0054]

[0055] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. Application of NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of liquid organic hydrogen carrier.

2. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 1, characterized in that: When used for catalytic hydrogenation and dehydrogenation, the NiCu@rGO / Mg(OH)2 composite catalytic material is mixed with a liquid organic hydrogen carrier to be hydrogenated or dehydrogenated to carry out catalytic hydrogenation or dehydrogenation.

3. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 2, characterized in that: When catalytic hydrogenation is performed, the reaction system consisting of the NiCu@rGO / Mg(OH)2 composite catalytic material and the liquid organic hydrogen carrier is in a hydrogen atmosphere; When catalytic hydrogenation is performed, the reaction system consisting of the NiCu@rGO / Mg(OH)2 composite catalytic material and the liquid organic hydrogen carrier is in a vacuum environment.

4. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 3, characterized in that: When catalytic hydrogenation and dehydrogenation are carried out, the reaction system is at a temperature of 150° C.-200° C., a pressure of 5 MPa-7 MPa, and a time of 5-7 hours.

5. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 2, characterized in that: The mass ratio of the NiCu@rGO / Mg(OH)2 composite catalytic material to the liquid organic hydrogen carrier is 1:8-12.

6. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 2, characterized in that: The liquid organic hydrogen carrier is ethylcarbazole.

7. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 1, characterized in that: The NiCu@rGO / Mg(OH)2 composite catalytic material is prepared by the following steps: (1) Methanol was added to Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, GO and PVP, fully dissolved, stirred and dried to obtain NiCu@GO powder. (2) placing the NiCu@GO powder obtained in step (1) into a tubular furnace and calcining it twice to obtain a bimetallic NiCu@rGO catalyst, (3) mixing the bimetallic NiCu@rGO catalyst obtained in step (2) with a Mg source, and ball milling the mixture to obtain an additive composite material of a Mg source-NiCu@rGO. (4) The Mg source-NiCu@rGO additive composite material obtained in step (3) is hydrolyzed, filtered, and dried to obtain a NiCu@rGO / Mg(OH)2 composite catalyst.

8. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 7, characterized in that: In step (1), the mass ratio of methanol, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, GO and PVP is 4-10:100-200:100-200:4-10:1, the stirring time is 4-10h, the rotation speed is 50-200rpm, the drying time is 10-24h, and the temperature is 50-100°C.

9. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 7, characterized in that: During the two calcinations in step (2), the first calcination was carried out in an Ar atmosphere at 4-10°C min -1 Heat to 400-600℃ at a heating rate of 1000℃, keep warm for 4-10h and then cool down naturally; The second calcination was carried out in a H2 / Ar atmosphere with a H2 ratio of 5% at 4-10°C min -1 Heat to 400-600℃ at a heating rate of 1000℃, keep warm for 4-10h and then cool down naturally.

10. The use of a NiCu@rGO / Mg(OH)2 composite catalytic material in catalytic hydrogenation and dehydrogenation of a liquid organic hydrogen carrier according to claim 7, characterized in that: In step (3), the Mg source is MgH2 or Mg, and the mass ratio of the bimetallic NiCu@rGO catalyst to the Mg source is 1:1-20; The ball milling is carried out under an argon atmosphere, with a ball-to-material ratio of 5-50:1, a ball milling speed of 300-500 rpm, and a ball milling time of 5-50 h; The drying temperature in step (4) is 40-100° C. and the drying time is 10-24 hours.